1967
DOI: 10.1042/bj1040534
|View full text |Cite
|
Sign up to set email alerts
|

Purification and amino acid composition of monomeric and polymeric collagens

Abstract: The preparations and amino acid compositions of highly purified tropocollagen and insoluble polymerized collagen are described. These collagens appear to be very suitable for comparative studies in an investigation of the cross-linkages that are introduced into tropocollagen during the formation of polymerized collagen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

1968
1968
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(22 citation statements)
references
References 13 publications
3
19
0
Order By: Relevance
“…Previously, both enzymatic and acid extraction methods have been used to obtain solubilized collagen for studies on collagen aging (6, 34). A number of studies have demonstrated that enzymatic extraction gives rise to subtle changes in the subsequent collagen products, although the gross physical characteristics of the molecules were not altered (35, 36). In this study, we used an acid extraction protocol, which ensures to prepare a native, nonpepsined, and fibrillar type I collagen.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, both enzymatic and acid extraction methods have been used to obtain solubilized collagen for studies on collagen aging (6, 34). A number of studies have demonstrated that enzymatic extraction gives rise to subtle changes in the subsequent collagen products, although the gross physical characteristics of the molecules were not altered (35, 36). In this study, we used an acid extraction protocol, which ensures to prepare a native, nonpepsined, and fibrillar type I collagen.…”
Section: Discussionmentioning
confidence: 99%
“…This preparation is referred to as "soluble collagen." (c) Acid-dispersible polymerized human adult skin collagen was extracted from cadaver skin by the Nishihara method as modified by Steven and Jackson (11,29). The term Nishihara collagen is used to refer to this preparation.…”
Section: Methodsmentioning
confidence: 99%
“…The samples were further extracted 3 times with 1.0M NaCl and 3 times with 0.1 M acetic acid using analogous volumes and procedure. The residue was dialyzed against a phosphate buffer (0.01 M) and fibrils were collected and purified from the insoluble material using the technique of Steven and Jackson [8]. The extracts obtained a t each salt and acid fractionation were separately pooled and centrifuged a t 65 000 x g for 60 min.…”
Section: Preparation Of Collagenmentioning
confidence: 99%